Childhood hearing loss - a Nigerian experience and a call to action (2013)
The burden of childhood hearing loss is huge, its effect on affected children devastating and the economic toll is heavy. Unfortunately much attention is not given to programs that promote early detection, management and rehabilitation of such children in developing countries. A cross-sectional study of the prevalence and patterns of hearing loss was undertaken among 127 children aged 5-15 years who presented for hearing assessment in two ear clinics in south-western Nigeria. Results revealed that majority (72.5%) of the children were confirmed as having hearing loss and 90.2% of those with hearing loss had disabling hearing loss. Conductive hearing loss was rampant but sensorineural hearing loss was the most prevalent. Although the flat audiogram and the flat tympanogram (Type B) predominated, other patterns of tympanograms and audiograms were also found. In conclusions, in developing countries there should be stronger advocacy by health workers for programs that will empower them and others who work with children to identify and refer children with hearing loss promptly. Universal screening of newborns and children should be made mandatory and programs aimed at preventing conditions and infections that can lead to childhood hearing loss should also be prioritized and strengthened as a matter of urgency.